Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

My friend needs help with this question and I don't know it.

share|improve this question
add comment

3 Answers

up vote 2 down vote accepted

If you use the definition of the hyperbolic cosine then, dropping the factor 2, you have:

$\exp(4x)+\exp(-4x) = (\exp(2x)-\exp(-2x))^2+2$

then,

$\exp(2x)-\exp(-2x) = (\exp(x)+\exp(-x))(\exp(x)-\exp(-x))$

if you do it you should get something like (if I'm not mistaken)

$\cosh(4x) = 8(\cosh(x))^2(\sinh(x))^2+1$

then, if you want to replace the $\sinh$ you can use the fact that $(\cosh(x))^2-(\sinh(x))^2=1$.

share|improve this answer
add comment

$$\cosh(2x)=2\cosh^2(x)-1$$

$$\cosh(4x)=2\cosh^2(2x)-1=2(2\cosh^2(x)-1)^2-1=8\cosh^4(x)-8\cosh^2(x)+1$$

share|improve this answer
add comment

For a mechanical way to translate the more familiar trigonometric identities to hyperbolic function identities, use $$\cosh x=\cos(ix),\qquad \sinh x=-i\sin(ix).$$

But perhaps an identity for $\cos(4w)$ does not qualify as familiar. However, it is easy to derive from standard facts: $$\cos(4w)=2\cos^2 (2w) -1=2(2\cos^2 w -1)^2-1.$$ Putting $w=ix$, we obtain in a mechanical way $$\cosh(4x)=2(2\cosh^2 x -1)^2-1.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.